Determination of TV Programme Ratings by Twitter - Kayahan, Dilek; Sergin, Asli; Diri, Banu (IEEE, 2013)
In this study, tweets retrieved form social media using Search API for selected TV programs are labeled as positive, negative or neutral according to the televiewer's comments, by the help of the calculated scores, the consistency of TV rating results will be tested. Sense analyzing method is used for classification. Specific words or phrases in tweets can make the tweet positive or negative otherwise they will be treated as neutral.
Keywords: Twitter; social media; classification; Engineering; Telecommunications